The role of the nutritional status of geriatric patients with gastrointestinal cancer in developing postoperative complications - Starčević, Sanja; Radovanović, Dragana; Škorić-Jokić, Svetlana; Mihalek, Nora; Golijanin, Danica (Archive of Oncology, 2023)
Background: Many studies have shown that geriatric patients with altered nutritional status are at higher risk of developing complications during medical treatment. Our study aimed to examine the role of preoperative nutritional status in developing postoperative complications and the length of hospital stay in geriatric patients who suffer from cancer and undergo major abdominal surgery. Methods: Prospective research was conducted at the Oncology Institute of Vojvodina from January 2020 until April 2021. This study included 82 patients over 65 years old, who were admitted to have radical surgery for gastrointestinal cancer performed. There were 6 patients excluded from the study. Nutritional status analysis was performed using BMI (Body mass index), preoperative serum albumin level, MNA-SF (Mini nutritional assessment- short form), and GNRI (Geriatric nutritional risk index). The classification of surgical complications was done using the Clavien-Dindo classification scale. Results: Of the total number of patients, 57 of them (75%) developed at least one surgical complication. Nonsurgical complications have been recognized in 28 patients (36.84%). Overweight patients, according to BMI, had a greater chance of developing grade I (p < 0.01) and grade II (p < 0.05) surgical complications of the Clavien-Dindo classification. Patients with normal serum albumin levels had a significantly lower chance of developing surgical complications of any grade (p = 0.00). BMI and MNA- SF were the most important predictors of delirium. Patients without GNRI risk (GNRI: >98) had a significantly lower chance of developing nonsurgical complications regarding comorbidity exacerbation (p = 0.03), and delirium (p = 0.00). Conclusion: None of the nutritional assessment tools used in our study were better or more efficient than the others in our sample of patients. Precise nutritional status assessment is complex and we cannot use only one scoring system or scale to get accurate results. Keywords: nutritional status, diagnosis, malnutrition, geriatric